0
$\begingroup$

I would like to solve $$f(x)=g(x)\cdot g(-x)$$ The goal is to express $g(x)$ in terms of $f(x)$. Any idea how to solve this?

$\endgroup$
4
  • $\begingroup$ There isn't a way to do this in general. $\endgroup$ Oct 13 at 23:53
  • $\begingroup$ Yes, there is no way unless g(-x) is the inverse of g(x) or equal to g(x) or anything similar. $\endgroup$ Oct 13 at 23:55
  • $\begingroup$ There is a solution only when $f \geq 0$ and $f(-x)=f(x)$. In this case $g(x)=\sqrt {f(x)}$ is the unique solution. $\endgroup$ Oct 14 at 0:01
  • $\begingroup$ You gave a rule to get $f$ from $g$. This can be understood as mapping $g \mapsto f$. You ask for a mapping $f \mapsto g$ (and it should be in some sense well behaved that you can write it down). However, your $g \mapsto f$ isn't even injective... $\endgroup$
    – user940347
    Oct 14 at 0:14
3
$\begingroup$

Assume $g$ is an arbitrary function $g:\mathbb{R} \to \mathbb{R}$ and $h^+$ is an arbitrary function $h^+:\mathbb{R^+} \to \mathbb{R}.$ Define $f:\mathbb{R} \to \mathbb{R}$ as $f(x):=g(x)g(-x)$. Now define $h:\mathbb{R} \to \mathbb{R}$ by $$h(x)=\begin{cases}h^+(x), &x>0\\g(0), &x=0\\ \frac{f(x)}{h^+(-x)},&x<0\end{cases}$$ We have $f(x)=h(x)h(-x)$, so it satisfies the same equation as $g$, but $h(x)$ is for positive $x$ an arbitrary function, so $g$ cannot be determined by $f.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.